Biogeography of culturable marine bacteria from both poles reveals that 'everything is not everywhere' at the genomic level. (22nd December 2021) - Qin, Qi‐Long; Wang, Zhi‐Bin; Cha, Qian‐Qian; Liu, Sha‐Sha; Ren, Xue‐Bing; Fu, Hui‐Hui; Sun, Mei‐Ling; Zhao, Dian‐Li; McMinn, Andrew; Chen, Yin; Chen, Xiu‐Lan; Zhang, Yu‐Zhong; et al.
Summary: Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept 'everything is everywhere'. However, whether the same OTUs from both poles have identical genomes, i.e. whether 'everything is still everywhere' at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium, Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that 'everything is not everywhere' at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.